Green product in Malaysia: Still a long way to go - Rajiani, Ismi (FONA-Social Ecological Research and German Federal Ministry of Education and Research (BMBF), 2011)
In the early 2000’s green technology is a buzz word. However in a developing country like Malaysia, customers’ acceptance of green products is still low due to the low number of environmentally friendly products acceptance compared to their non-green counterparts. On the basis of benefit and cost analysis, the purpose of this study is to identify the factors influencing customers’ decision in buying green product. This study argues that customers’ intention to buy green products are determined by benefit-toself, benefit to environment, comparative cost and attainable cost. A survey is based on sample of 360 customers and potential customers of green products in Melaka, Malaysia and Structural Equation Model is used. The research revealed that the benefit-to-self factor is not a significant factor which influences customers’ intention to buy green products. The implication of this research to the design of green products is then discussed.